Poetics of Place in the Works of John Betjeman - Kubová, Dominika (Univerzita Pardubice, 2016)
The aim of this bachelor paper is to provide an analysis of John Betjeman's poetry to trace topographical elements in his work. The first chapter provides a historical and cultural background concerning the shift from Victorian to post-war Britain, focusing on demographic changes in urban and rural life. Then, the transformation of Victorian and modern architecture is examined. The analytical part explores Betjeman's relation to different places, specifically to cities, suburbs and the countryside and his perception of architecture, especially ecclesiastical.
Poetika místa v díle Johna Betjemana
Keywords: Betjeman, John; Victorian Britain; post-war Britain; place; landscape; architecture; poetry; Betjeman, John; viktoriánská Británie; poválečná Británie; místo; krajina; architektura; poezie